2019
DOI: 10.1002/jcb.29252
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of methylation‐driven genes for predicting the prognosis of patients with head and neck squamous cell carcinoma

Abstract: To help provide evidence for prognosis prediction and personalized targeted therapy for patients with head and neck squamous cell carcinoma (HNSCC), we investigated prognosis-specific methylation-driven genes in HNSCC. Survival time data, RNA sequencing data, and methylation data for HNSCC patients were downloaded from The Cancer Genome Atlas. The MethylMix R package based on the β mixture model was utilized to screen genes with different methylation statuses in tumor tissues and adjacent normal tissues, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Zhu in 2019 found out that the combined analysis of the methylation status of 5 genes (CENPV, SYTL2, OCLN, CASD1, and TUB) helped in the construction of a risk prediction model of the prognosis of OSCC [38] Pan et al in 2019 reported that subsequent combined survival analysis on six genes (INA, LINC01354, TSPYL4, MAGEB2, EPHX3, and ZNF134) could be used as independent prognostic markers and potentially used as drug targets [39].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu in 2019 found out that the combined analysis of the methylation status of 5 genes (CENPV, SYTL2, OCLN, CASD1, and TUB) helped in the construction of a risk prediction model of the prognosis of OSCC [38] Pan et al in 2019 reported that subsequent combined survival analysis on six genes (INA, LINC01354, TSPYL4, MAGEB2, EPHX3, and ZNF134) could be used as independent prognostic markers and potentially used as drug targets [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, classical factors of head and neck tumors were not taken into account in the study. Moreover, reports [ 30 ] showed that different methylation status by the MethylMix R package based on the β mixture model constructed using six genes (INA, LINC01354, TSPYL4, MAGEB2, EPHX3, and ZNF134) could predict OS in HNSCC patients. However, the area under the curve (AUC) for the model was only 0.723.…”
Section: Discussionmentioning
confidence: 99%
“…MethylMix is a program designed to identify methylation events related to gene expression. 12 We explored the association between DNA methylation and gene expression. Pearson coefficient between methylation level (β value) and gene expression level was calculated to find significantly negatively related genes using the MethylMix package in R. Pearson coefficient < −0.3 with P < .05 was set as the criterion for methylation-related DEGs identification.…”
Section: Methodsmentioning
confidence: 99%